Pathomorphological changes of the placenta during coronavirus disease (COVID 19) in pregnant women at 33-40 weeks of gestation - Savchuk , Tetiana; Gychka , Sergiy (The Ukrainian Scientific Medical Youth Journal, 2024)
the results of recent studies indicate that COVID-19 in pregnant women up to the 35th week of gestation is a risk factor for intrauterine infection and antenatal asphyxia of the fetus. Therefore, the aim of our research was to determine the pathomorphological changes of the placenta during the coronavirus disease (COVID-19) in pregnant women at 33-40 weeks of gestation in order to establish the mechanisms of formation of placental function disorders up to the 35th week of pregnancy. The material of the study is 37 placentas of live-born babies of women with clinical manifestations of coronavirus disease during this pregnancy, confirmed by a positive PCR test (determination of SARS-CoV-2 RNA). Placentas were obtained after informed consent at the Department of Pathological Anatomy of the National Specialized Children’s Hospital “Ohmatdyt” of Ukraine in the period from November 2020 to December 2021. Placentas of women with gestosis of pregnant women were not included in the study group. The material was divided into groups depending on the duration of the disease: Group I – COVID-19 at 33-34 weeks, Group II – COVID-19 at 35-40 weeks of gestation. 36 infants were born with high Apgar scores (8-9) and a negative PCR test, despite the fact that 3 pregnant women had a severe course of the disease with pneumonia. One child was assessed on the Apgar scale of 3-4 points and had a positive PCR test, the mother’s clinical manifestations were moderate-severe. Research methods were used: macroscopic, organometric, microscopic with staining with histological dyes – hematoxylin and eosin (H&E). The immunohistochemical method was used using monoclonal antibodies to CD34 and smooth muscle actin to determine the condition of the endothelium of arterioles and the muscle layer. Pathomorphological changes in the placentas of live births with COVID-19 in both groups were characterized by exudative inflammation (placentitis), the severity of which was assessed by the number of pluses (from 1 to 5). The intensity of inflammatory changes decreased with the increase in the duration of the post-COVID interval (the time interval from the diagnosis of COVID-19 in a pregnant woman to delivery). Infection with a coronavirus (SARS-CoV-2) and damage to the intermediate villi led to dissociated villous maturation disorders in the placenta, which was characterized by local hypoplasia of terminal villi; the average number of which in one field of view at a magnification of 400 in group I was 20.35 [11; 29], against 25.0 [21; 29] in the II group, p1-2 =0.001, which was noted in 58.8% (95% CI: 33.5%-81.9%), р1-2=0.005. In the work, the mechanism of disruption of chorion formation during COVID-19 in pregnant women at 33-40 weeks of gestation is determined. In our opinion, before the 35th week of pregnancy, COVID-19 causes the SARS-CoV-2 coronavirus to damage the mature intermediate villi of the chorion and the impossibility of formation from the last terminal villi, which is the cause of placental dysfunction (distal villous immaturity delay). This was confirmed by a sufficient number of terminal villi in placentas with COVID-19 after the 35th week of pregnancy. In both groups, the birth of babies with high Apgar scores was ensured by compensatory mechanisms of the placenta and focal inflammatory changes. Taking into account the probability of occurrence of local hypoplasia of terminal villi with COVID-19 in a pregnant woman up to 35 weeks, clinicians should remember that this period is critical for the formation of the placenta and for perinatal losses. Placentas with COVID-19 in the 1st and 2nd trimesters of pregnancy require further investigation.